Taxonomy and phylogeny of Dothideomycetes - Mckenzie, Eric H.c.; Jones, E.b. Gareth; Hyde, Kevin D. (Phytotaxa, 2014)
The ascomycete class Dothideomycetes comprises a highly diverse range of fungi characterized mainly by bitunicate asci, usually with fissitunicate dehiscence. Species are saprobes, with many asexual states comprising extremely important plant pathogens. They are also endophytes, epiphytes, fungicolous, lichenized, or lichenicolous fungi. They occur worldwide in terrestrial, freshwater and marine habitats. Until recently the taxonomy of Dothideomycetes was confused and based mostly on a limited number of morphological characters. Molecular data has been recently incorporated into their study and a more natural phylogeny of the group is emerging. The recent monograph of 105 families by Hyde and co-workers (2013), with a phylogenetic tree based on four genes, has advanced the understanding of this group and kick-started further studies.